Diabetic Peripheral Neuropathy: Epidemiology, Physiopathology, Diagnosis and Treatment - Akter, Nazma (Delta Medical College Journal, 2019)
Diabetic peripheral neuropathy (DPN) is a common complication of both type 1 and type 2 diabetes. It affects over 90% of the diabetic patients. It is widely accepted that the toxic effects of hyperglycemia play an important role in the development of this complication, but several other hypotheses have been postulated. It is typically characterized by significant deficits in tactile sensitivity, vibration sense, lower-limb proprioception, and kinesthesia. Painful DPN has been shown to be associated with significant reductions in overall quality of life, increased levels of anxiety and depression, sleep impairment, and greater gait variability. DPN is often misdiagnosed and inadequately treated. Clinical recognition of DPN is imperative for allowing timely symptom management to reduce the morbidity associated with this condition. The management of diabetic neuropathic pain consists basically in excluding other causes of painful peripheral neuropathy, improving glycemic control as a prophylactic therapy and using medications to alleviate pain. First line drugs for pain relief include anticonvulsants, such as pregabalin and gabapentin and antidepressants, especially those that act to inhibit the reuptake of serotonin and noradrenaline. In addition, there is experimental and clinical evidence that opioids can be helpful in pain control, mainly if associated with first line drugs. Other agents, including for topical application, such as capsaicin cream and lidocaine patches, have also been proposed to be useful as adjuvant in the control of diabetic neuropathic pain, but the clinical evidence is insufficient to support their use. The purpose of this review is to examine proposed mechanisms of DPN, summarize current treatment regimen. A better understanding of the mechanisms underlying diabetic neuropathic pain will contribute to the search of new therapies. Delta Med Col J. Jan 2019 7(1): 35-48